Is there still a place for open surgery in the treatment strategy of rectal cancer? - Andrzej Kawiński; Łukasz Dziki; Radzisław Trzciński; Adam Dziki; Michał Mik (Gastroenterology Review)
Over the last 30 years laparoscopic surgery of rectal cancer has been progressively gaining popularity due to expanding experience and the development of technical skills according to the surgeons’ learning curves. The report constitutes a review of recently published articles concerning surgical techniques in colon cancer, with special emphasis on rectal cancer treatment. We tried to address the question of whether, in view of further development and broader use of laparoscopic surgery, there still is a place for open surgery in the treatment strategy of rectal cancer.